Author correction: Large-scale transcriptome-wide association study identifies new prostate cancer risk regions - Mancuso, Nicholas; Brenner, Hermann (Nature Communications, 2019)
The original version of this Article contained an error in the spelling of a member of the PRACTICAL Consortium, Manuela Gago-Dominguez, which was incorrectly given as Manuela Gago Dominguez. This has now been corrected in both the PDF and HTML versions of the Article. Furthermore, In the original HTML version of this Article, the order of authors within the author list was incorrect. The consortium PRACTICAL consortium was incorrectly listed after Bogdan Pasaniuc and should have been listed after Kathryn L. Penney. This error has been corrected in the HTML version of the Article; the PDF version was correct at the time of publication.
The PRACTICAL consortium: Hermann Brenner [und weitere]
Hermann Brenner ist Mitglied des PRACTICAL consortium
Gesehen am 05.07.2019